Bats mimic hymenopteran insect sounds to deter predators - Ancillotto, Leonardo (2022)
This study explores interspecific acoustic mimicry in mammals, particularly focusing on the greater mouse-eared bat (Myotis myotis) distress calls. These calls imitate stinging bee and wasp sounds, aiming to deter avian predators. While visual mimicry is well-documented, acoustic mimicry, a less-studied phenomenon, can also play a significant role in predator-prey interactions. The study identifies the similarities in distress calls between the bat and hymenopteran insects, and experiments with captive owls reveal their avoidance response to these mimicry-induced sounds. This research sheds light on a novel form of mimicry involving mammals and insects, adding to the understanding of the intricate relationships in the natural world.